Elaboración de un plan estratégico para la empresa supermercado Yerovy de la ciudad de Loja - Montalván Mendoza, Ana María (2016)
Today is of vital importance that companies have a Strategic Plan as a key tool for achieving the goals of any business or organization. Is why this thesis aims at general: "develop a Strategic Plan for the company YEROVY supermarket in the city of Loja, marketer of products of first necessity", in order to contribute to the organizational development of the company in study. Within the specific objectives that have been proposed have: "a situational diagnosis of the company YEROVY supermarket in the city of Loja"; " " Carry out an analysis of the factors external (EFE) affecting the activity developed by the company in study"; "An analysis of the factors internal (EFI) identifying the strengths and weaknesses of the company supermarket Yerovy';' " Company SWOT analysis Supermarket Yerovy " from the city of Loja"; "Developing the high impact matrix that allows the strategic objectives for the investigated company"; "To develop the strategic objectives in order to obtain a better performance in the marketing of the products offered by the company"; and "the budget required to implement the enterprise Strategic Plan supermarket Yerovy from the city of Loja". In order to meet the objectives set were used the following methods and techniques, so we have: the deductive, inductive, analytic, statistical and systematic method. Among the techniques was applied the bibliographical collection to collect the necessary information about strategic planning, through direct observation visits field to the supermarket "YEROVY" company, more than this survey applied to customers and employees of the supermarket "YEROVY" company, and interview the Manager of the same Eng. Maria Luisa Torres Torres. Then presents the results of the information obtained, where took place the Situational diagnosis of the company that allows you to analyze the external aspects of the environment, thus same the internal aspects, in order to establish the current status of the company is. So we have the EFE matrix with a value of 2,77 points which means that there is a predominance of the opportunities the threats; While the matrix EFI with a value of 2.89 points which means that there is a predominance of strengths over weaknesses. So as to later formulate strengths, weaknesses, opportunities and threats, for the matrix SWOT, the same design which allowed to determine the strategic objectives with their respective budgets and responsible; so we have: " " Establish the mission and vision for the company, in order to improve the corporate image of the company"; "Carry out promotional and advertising programs that allow to know the products marketed by the company"; "Develop a training plan for employees of the supermarket YEROVY"; "Establish a plan of motivation and incentives for the staff of the company"; and finally "implement the use of uniform for the staff of the company". Should be noted that the implementation of the five strategic goals has a cost of $12.961,00. Finally there is concerning the conclusions and recommendations, where arises, the Manager of the company supermarket "YEROVY" the importance of the implementation of the Strategic Plan, since this will allow you to position itself in the minds of consumers and subsequently reach your loyalty. In such a way that will increase the sales and profits of the company.